A Reporter System for Fast Quantitative Monitoring of Type 3 Protein Secretion in Enteropathogenic E. coli - Luit Barkalita; Athina G. Portaliou; Maria S. Loos; Biao Yuan; Spyridoula Karamanou; Anastassios Economou (Microorganisms, 2020)
The type 3 secretion system is essential for pathogenesis of several human and animal Gram-negative bacterial pathogens. The T3SS comprises a transmembrane injectisome, providing a conduit from the bacterial cytoplasm to the host cell cytoplasm for the direct delivery of effectors (including toxins). Functional studies of T3SS commonly monitor the extracellular secretion of proteins by SDS-PAGE and western blot analysis, which are slow and semi-quantitative in nature. Here, we describe an enzymatic reporter-based quantitative and rapid in vivo assay for T3SS secretion studies in enteropathogenic E. coli (EPEC). The assay monitors the secretion of the fusion protein SctA-PhoA through the injectisome based on a colorimetric assay that quantifies the activity of alkaline phosphatase. We validated the usage of this reporter system by following the secretion in the absence of various injectisome components, including domains of the gatekeeper essential for T3SS function. This platform can now be used for the isolation of mutations, functional analysis and anti-virulence compound screening.